Monitoring wellness, training load and neuromuscular performance: Implications for assessing athlete training status - Lombard, Wayne (Department of Human Biology, 2022)
Background: Athletes training for peak performance have periods of systematic overload followed by recovery. The balance between overload and recovery is important to avoid unexpected fatigue or underperformance. The relationship between overload and recovery is unique for each athlete. Thus, programmes designed to monitor fitness and fatigue should consider the inter-athlete differences. Aim: The broad aim of the PhD thesis was to assess the relationships between various tools for monitoring fitness and fatigue in elite level athletes. Subjective and objective training/match demands, questionnaires to assess wellness and readiness-to-train as well as countermovement jump variables to assess neuromuscular performance were investigated within 4 inter-related studies. Methods: Four inter-related studies were designed to determine; 1) the validity and reliability of countermovement jump variables measured on a force plate in the laboratory; 2) the relationships between countermovement jump variables, responses to a wellness and readinessto-train questionnaire and exercise-induced fatigue in the laboratory; 3) the relationships between training load, responses to a wellness and readiness-to-train questionnaire and neuromuscular performance in elite level female field hockey athletes measured in a “realworld” situation, and 4) the relationships between these same variables for each athlete and whole team before, during and after international match play. Primary findings: The findings for each inter-related study were as follows; 1) Maximum force, rate of force development, jump height, flight time and time to maximum force, as measured on a force plate during a countermovement jump were valid and reliable. The typical error of measurement was defined for each variable. The validity and reliability were best in participants who had more strength training experience. In most cases the precision of the variables was sufficient to detect “small” changes. 2) Subjective measures (wellness questionnaire) were more sensitive to acute exercise-induced fatigue compared to objective measures of neuromuscular performance; 3) The relationship between variables differed between players. Multiple variables should be collected to better understand a player's subjective and objective fitness and fatigue status in response to subjective and objective measures of match and/or training demands; 4) Pre, intra and post-match related data should be collected to better understand individual player responses between matches. Variables such as jump height, rating of perceived exertion, total distance during the match, bodyload (a derived measure of the total external mechanical stress from accelerations, decelerations and change of direction) and subjective wellness should be considered when monitoring athlete training status. Conclusions: Firstly, there is no set standard battery of tools that can be used to monitor fitness and fatigue of athletes as the relationship between variables is not consistent between athletes. Variables such as jump height, rating of perceived exertion, total distance, bodyload and wellness responses should be considered in a monitoring system. Secondly, this thesis proposes the novel concept of “monitoring specificity”. This suggests that different tools, based on their responsiveness, should be used at an individual level. Thirdly, identifying which athletes are most sensitive to certain variables will reduce the “noise” within a team's monitoring system. This will enable better informed decisions to be made about the athlete's fitness/fatigue status.